2007
DOI: 10.1111/j.1469-8749.2007.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and health‐related quality of life of adolescents with cerebral palsy

Abstract: This study assessed quality of life (QOL) and health-related quality of life (HRQOL) of 203 adolescents with cerebral palsy (111 males, 92 females; mean age 16y [SD 1y 9mo]). Participants were classified using the Gross Motor Function Classification System (GMFCS), as Level I (n=60), Level II (n=33), Level III (n=28), Level IV (n=50), or Level V (n=32). QOL was assessed by self (66.5%) or by proxy (33.5%) with the Quality of Life Instrument for People With Developmental Disabilities, which asks about the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 27 publications
7
99
1
4
Order By: Relevance
“…Almost two-thirds of the sample of children was male, and almost half had mild motor impairments (level I GMFCS). Not surprisingly, the children who were able to complete the PedsQL were somewhat older, had less functional limitations in motor, social, communication, and daily living skill domains, and were more likely to be integrated into regular schools compared to children who were unable to complete questionnaires (similar to Rosenbaum et al [29]). Of the 48 families in which a parent and child completed the PedsQL, 31.3% of mothers and 45.5% of fathers had high school education only, and 61.7% of mothers and 93.2% of fathers were employed.…”
Section: Group Characteristicsmentioning
confidence: 62%
“…Almost two-thirds of the sample of children was male, and almost half had mild motor impairments (level I GMFCS). Not surprisingly, the children who were able to complete the PedsQL were somewhat older, had less functional limitations in motor, social, communication, and daily living skill domains, and were more likely to be integrated into regular schools compared to children who were unable to complete questionnaires (similar to Rosenbaum et al [29]). Of the 48 families in which a parent and child completed the PedsQL, 31.3% of mothers and 45.5% of fathers had high school education only, and 61.7% of mothers and 93.2% of fathers were employed.…”
Section: Group Characteristicsmentioning
confidence: 62%
“…Niewczyk and Granger 2) noted the importance of a clear definition of terms when assessing outcomes, stating that function refers to a person's ability to perform basic daily living skills such as eating, toileting, grooming, walking, and interacting with others, whereas HRQOL refers to an overall assessment of well-being across various domains such as physical and psychosocial well-being 3) . Most research related to the quality of life or HRQOL, for individuals with CP has shown that physical well-being is positively correlated with mobility and that mobility dose not correlate consistently with psychosocial well-being [4][5][6][7] . Grilli et al 8) reported associations between activities of daily living (ADL) and HRQOL using the functional independence measure (WeeFIM) and the pediatric quality of life inventory (PedsQL4,0) individually for children with global developmental delay.…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid conditions, such as seizure disorders, hearing impairments, abnormal muscle tone, or postural instability, can be present. 17 Any of these factors (or multiple combinations) can affect eating and swallowing skills, leading to nutritional compromise. 18 Feeding problems for children who have cerebral palsy may manifest as oral fluid/food spillage while feeding, increased length of meals (often confused as "behavioral"), coughing/gagging with feeding, recurrent lower respiratory infections, GER, and/or nasal reflux from the posterior pharynx.…”
Section: Children Who Have Cerebral Palsymentioning
confidence: 99%
“…Neither clinicians nor researchers have yet to agree on a universal definition of either QOL or HRQOL. For purposes of this article, the following are general descriptions: QOL: the overall sense of well-being, including aspects of happiness and satisfaction with life as a whole HRQOL: aspects of QOL that affect health (physical or mental) or are affected by health and that are associated with life satisfaction 17,24 Petersen et al described caregivers' perceptions of nonoral feeding for children who have developmental disabilities.…”
Section: Shared Decision-making: a Multifactorial Processmentioning
confidence: 99%